DARI RUANG PERIKSA KE RUANG SIDANG: KAJIAN YURIDIS KEKERASAN SEKSUAL BERBASIS RELASI KUASA OLEH DOKTER SERTA MEKANISME PERLINDUNGAN TERHADAP KORBAN - Hasanah, Nur Hafizal; Fijrah, Nurul; Sinar, Sinar; Nurisnaeni, Nurisnaeni; Adzan, Adzan; Selfi, Selfi (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2025)
Sexual violence is a form of human rights violation that is underpinned by power relations. In the medical context, the power relationship between doctors and patients is unequal, as doctors have authority over patients' bodies, personal information, and treatment decisions. This places patients in a passive, dependent, and vulnerable position, opening the door to abuse of power. The phenomenon of alleged sexual violence by doctors shows that unequal power relations are often the root cause of sexual violence. This study aims to examine and analyze legal regulations related to power-based sexual violence by doctors, as well as forms of legal protection and recovery for victims. The method used is normative jurisprudence with a legislative approach and conceptual analysis. Legally, Indonesia has a Sexual Violence Criminal Law (TPKS Law) that recognizes power relations as an aggravating factor in sentencing. The new Criminal Code also emphasizes that unequal power relations can constitute psychological violence or coercion, not just physical violence. Therefore, any sexual act by a doctor towards a patient without medical grounds and valid consent constitutes a serious violation of criminal law, medical ethics, and the principles of medical professionalism. Legal protection under the UU TPKS includes prevention, prosecution, recovery, and rehabilitation of victims, so that the interests of victims are placed as an aspect that must be considered in criminal and social policy.